Taxation of human capital and wage inequality: A cross-country analysis - Fatih Guvenen; Burhanettin Kuruscu; Serdar Ozkan (Institute for Fiscal Studies (IFS), 2009)
Wage inequality has been significantly higher in the United States than in continental European countries (CEU) since the 1970s. Moreover, this inequality gap has further widened during this period as the US has experienced a large increase in wage inequality, whereas the CEU has seen only modest changes. This paper studies the role of labor income tax policies for understanding these facts. We begin by documenting two new empirical facts that link these inequality differences to tax policies. First, we show that countries with more progressive labor income tax schedules have significantly lower before-tax wage inequality at different points in time. Second, progressivity is also negatively correlated with the rise in wage inequality during this period. We then construct a life cycle model in which individuals decide each period whether to go to school, work, or be unemployed. Individuals can accumulate skills either in school or while working. Wage inequality arises from differences across individuals in their ability to learn new skills as well as from idiosyncratic shocks. Progressive taxation compresses the (after-tax) wage structure, thereby distorting the incentives to accumulate human capital, in turn reducing the cross-sectional dispersion of (before-tax) wages. We find that these policies can account for half of the difference between the US and the CEU in overall wage inequality and 76% of the difference in inequality at the upper end (log 90-50 differential). When this economy experiences skill-biased technological change, progressivity also dampens the rise in wage dispersion over time. The model explains 41% of the difference in the total rise in inequality and 58% of the difference at the upper end.
Keywords: 330; Wage Inequality; Human Capital; Skill-Biased Technical Change; Tax Policies; Steuerpolitik; Einkommensteuer; Humankapital; Lohnniveau; Einkommensverteilung; Soziale Ungleichheit; USA; EU-Staaten